Long-lasting effects of in utero heat stress on subsequent performances of heifers and primiparous cows - A. Vinet; C. Fouéré; B.C.D. Cuyabano; S. Mattalia; R. Vallée; A. Barbat; C. Bertrand; C. Hoze; D. Boichard (Journal of Dairy Science)
ABSTRACT: The performance of an adult dairy cow may be influenced by heat stress that occurs during her gestation. The present study investigated potential effects of temperature-humidity index (THI) experienced by a cow during pregnancy on the gestated daughter's performance on her first lactation, for the French Holstein and Montbéliarde dairy cattle populations. We analyzed 14 traits, all measured on genotyped cows: 305-d milk, fat, and protein yields; 305-d SCS; clinical mastitis (both occurrence and number of events); body conformation traits; and heifer and cow conception rate. To study the effect of heat stress, we considered the THI experienced by the gestating cow, averaged for each month of her pregnancy and then categorized in 7 classes (≤40, [40,45], [45,50], [50,55], [55,60], [60,65], and >65). These average THI classes were then fitted as categorical covariates in the regression models used for this study, which included other fixed effects, and the GEBV as a covariate, both specific to each trait, the latter being previously obtained from the official French evaluations. The THI effect was therefore estimated as the deviation between the observed and predicted performances. In general, the estimated heat stress effects were small, presenting limited practical impact on the studied traits, and particularly for fertility and udder health, the estimated heat stress effects were not statistically significant. For the production traits (i.e., milk, fat, and protein yields), the estimated effect associated with high THI experienced at the beginning of the gestation was negative, and slightly positive when associated with high THI experienced by the dam at the end of her pregnancy. Finally, our results suggest that under the current French climate conditions, heat stress experienced by cows during any stage of their pregnancy has limited impact on the future performance of their gestated daughters; however, we cannot exclude that a significant in utero heat stress effect may be present in climate conditions warmer than the French.